Comparison of venous thromboembolism incidence in newly diagnosed multiple myeloma patients receiving bortezomib, lenalidomide, dexamethasone (RVD) or carfilzomib, lenalidomide, dexamethasone (KRD) with aspirin or rivaroxaban thromboprophylaxis. (15th August 2021) - Piedra, Katrina; Peterson, Tim; Tan, Carlyn; Orozco, Jennifer; Hultcrantz, Malin; Hassoun, Hani; Mailankody, Sham; Lesokhin, Alexander; Shah, Urvi; Lu, Sydney; Patel, Dhwani; Derkach, Andriy; et al.
Summary: Incidence of venous thromboembolism (VTE) varies across different regimens in newly diagnosed multiple myeloma (NDMM) patients. Limited data exist on the use of direct oral anticoagulants as thromboprophylaxis in the setting of haematologic malignancies, specifically multiple myeloma. In this retrospective study of 305 NDMM patients, VTE rates in those treated with carfilzomib, lenalidomide, dexamethasone (KRD) + aspirin (ASA), bortezomib, lenalidomide, dexamethasone (RVD) + ASA, and KRD + rivaroxaban were statistically significant, 16·1%, 4·8%, and 4·8%, respectively. The findings confirm a higher incidence of VTE when using KRD induction compared to RVD induction and reveal that the use of low‐dose rivaroxaban thromboprophylaxis can mitigate this risk without an observable increase in bleeding rates.